Low-lying energy levels of 229Th35+ and the electronic bridge process. (28th June 2021) - Porsev, S G; Cheung, C; Safronova, M S
Abstract: The nuclear transition between the ground and the low-energy isomeric state in the 229 Th nucleus is of interest due to its high sensitivity to a hypothetical temporal variation of the fundamental constants and a possibility to build a very precise nuclear clock, but precise knowledge of the nuclear clock transition frequency is required. In this work, we estimate the probability of an electronic bridge (EB) process in 229 Th 35+, allowing to determine the nuclear transition frequency and reduce its uncertainty. Using configuration interaction methods, we calculated energies of the low-lying states of Th 35+ and determined their uncertainties. Our calculations showed that the transition energy from the J = 15/2 state to the ground state, 8.31 eV, is close to the central value of the experimentally determined nuclear isomer energy, 8.19 eV, and practically coincides with the upper edge value, 8.31 eV. It opens new possibilities for a more precise measurement of the nuclear isomer energy using an EB process.